Social Egg Freezing in Islamic Law: Conditional Permissibility through a Maqāṣid al-Sharī‘ah and Gender Justice Perspective - Ridha Aulia; Ilzam Hubby Dzikrillah Alfani; Muhammad Ruhiyat Haririe; Denny Iswanto; Neng Hannah (Universitas Muhammadiyah Bandung, 2025)
This study analyzes the practice of social egg freezing for unmarried women from the perspective of Islamic law and its relevance to maqāṣid al-sharī'ah and gender justice. The phenomenon of modernity has led Muslim women to delay marriage and pregnancy for education and careers, creating tension between professional demands and biological reproductive limitations. This qualitative research employs a library-based method with a normative-theological approach, integrating tafsir, maqāṣid al-sharī'ah, qiyās, and sadd al-dharī'ah. Data were obtained from primary sources including Qur'anic verses, classical and contemporary tafsir works, and authoritative fatwas, supported by modern scientific literature. The findings indicate that social egg freezing can be understood as a form of human agency (ikhtiyar) to preserve reproductive potential while responding to the social realities of modern women. Legally, this practice falls within the framework of the